Supervisor’s Emotional Intelligence and Personality of Supervisor as Determinants of Employee Job Anxiety: A Systematic Literature Review - J.K.S.P, Somasiri; G.A.T.R, Perera (Asian Journal of Interdisciplinary Research, 2022)
The employee job anxiety has been a concept which has been gain more attention in the present world specially in relation with the changes of environment and economy. Available literature has been provided evidence to prove the fact that supervisors can be anxiety provoking factor within organization and emotional intelligence and personality can shaped the behavior of supervisors. However, despite the available evidence there were no reviews to be found in relation to this area. Hence, this review aims to highlight the gap in the existing empirical studies and to provide suggestions for future research. This study has conducted the review by searching papers through Google Scholar and Emerald Insight which have been published in 1990-2022. As with the findings of selected articles the gap in the existing studies have been able to be highlighted and there were many empirical studies were available in relation to job anxiety. Accordingly, suggestions for future studies have been given based on the findings of the review.